IDENTIFIKASI KESALAHAN MAHASISWA DALAM MENYELESAIKAN SOAL-SOAL PADA MATA KULIAH GEOMETRI ANALITIK - Asep Ikin Sugandi; Deddy Sofyan; Linda Linda; Dewi Ratna Sari (IKIP Siliwangi, 2022)
The purpose of this study is to describe the errors made by students when solving problems on the material of circles and conic sections. The method used in this study is a qualitative descriptive method. The subjects in the study consisted of 30 students of the Mathematics Education Study Program, IKIP Siliwangi Bandung. The instrument of this research is a written test in the form of a description of 4 questions. The data processing was carried out in three stages, namely the reduction stage, the presentation and drawing conclusions from the data. Based on the results of the study, it showed that students' errors in solving analytic geometry problems consisted of conceptual, procedural and technical errors. The causes of conceptual errors are student errors in stating the formula used when solving the problems presented, students do not understand the material and do not know how to solve problems. The cause of procedural errors is that students lack practice when completing the given practice questions, students do not understand the process of solving problems correctly. The cause of technical errors is the lack of skill of students in the process of calculating in an operation and students' inaccuracy in the calculation process, less thorough and in a hurry when solving problems so they do not re-check what has been done